Silicone composition and method for producing composite molded articles

A silicone composition with specific organopolysiloxanes and a unique binder achieves durable bonding to polycarbonate and polybutylene terephthalate without surface pretreatment, ensuring reliable demolding and economic efficiency.

JP7614179B2Active Publication Date: 2025-01-15WACKER CHEMIE AG
View PDF 19 Cites 0 Cited by

Patent Information

Application Number
JP2022510982
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2019-08-19
Publication Date
2025-01-15
Estimated Expiration
2039-08-19

AI Technical Summary

Technical Problem

Existing methods for bonding silicone compositions to substrates often require additional processing steps, such as surface pretreatments, which can alter the substrate's physical and chemical properties, and may involve toxic additives unsuitable for pharmaceutical, cosmetic, or food-related applications.

Method used

A silicone composition comprising organopolysiloxanes with specific Si-H content and a unique binder, which allows for strong adhesion to substrates like polycarbonate and polybutylene terephthalate without requiring surface pretreatment, using a combination of components (A, B, C, and D) that includes a hydrosilylation catalyst and a specific binder (D) to achieve durable bonding.

Benefits of technology

The composition enables reliable demolding operations with minimal adhesion to processing equipment, ensuring high manufacturing stability and economic efficiency by providing strong adhesion to substrates like polycarbonate and polybutylene terephthalate without the need for toxic additives.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to silicone compositions and methods for producing composite materials, such as two-component moldings made of soft addition-crosslinkable silicone elastomers combined with hard thermoplastics, such as polyamides, polycarbonates, and polybutylene terephthalates.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a silicone composition and a method for producing composite materials, such as two-component molded articles made from soft addition-crosslinkable silicone elastomeric polyamides in combination with rigid thermoplastics, such as polycarbonate and polybutylene terephthalate. [Background technology]

[0002] Composite articles made of various materials are important engineering materials. The requirement that these materials must meet is a firm bond between the individual base materials that is durable under appropriate use conditions. When the silicone composition contacts the mold during processing, such as in the processing of two-component injection molding of thermoplastics and silicone, the adhesion of silicone or composite to the mold is also undesirable.

[0003] Possible base materials are, for example, metals, glasses, ceramics, organic polymers or biological materials, and also silicones or crosslinkable silicone compositions, however, in the case of silicones, a lasting bond to other substrates is difficult due to the non-adhesive properties of silicones.

[0004] EP0961811B1 describes a storage-stable addition-crosslinking silicone composition and its use as a hydrophilic impression material for the human body, for example for dental impression materials. In this application, therefore, the non-stick properties of the silicone composition are beneficial, since poor and therefore reversible adhesion to surfaces, such as tooth enamel and dental polymers, metals and ceramics, is explicitly required.

[0005] Many techniques are known from the literature for obtaining strong and durable bonds between silicones and other underlying materials.

[0006] In principle, it is possible to modify the chemistry and physical properties of the underlying material in order to improve the adhesion between the silicone and the underlying material.

[0007] Exemplary methods include pre-treating the surface of the base material using UV irradiation, flame treatment, corona treatment or plasma treatment. In such pre-treatment steps, the surface or a layer close to the surface of the base material is activated, i.e. functional groups, mainly polar groups, are created, which allow the formation of bonds and in this way make it possible to achieve a permanent composite material.

[0008] Another method to produce a durable, strong silicone composite is the application of a primer to the base material, but such primers often contain solvents in addition to adhesion-promoting additives, and these solvents must be removed again after application to the base material.

[0009] A drawback of all these methods is the need for additional processing steps as a result of the pretreatment of the substrate, which can be avoided by suitable functional groups contributing to adhesion in the production of the composite article provided in bulk or on the surface of the silicone or underlying material.

[0010] However, this procedure is only described as requiring at least one structural modification of the substrate, which may result in adverse effects on physical and chemical properties. Moreover, chemical modification of polymers is sometimes not without its difficulties.

[0011] Another way to achieve adhesion between silicone and polymeric substrates is the addition of certain additives, known as bonding agents, and / or certain crosslinking agents. These additives, mixed with the non-crosslinked silicone composition, make the silicone composition adhere to the underlying material during or after vulcanization, sometimes only after storage.

[0012] As a result, the chemical nature of the materials involved in the composite is not critically affected, and further pretreatment of the base materials is generally not necessary.

[0013] For example, DE 102007044789 describes self-adhesive, addition-crosslinking silicone compositions that exhibit very good adhesion to engineering plastics, especially plastics based on bisphenol A. Here, a mixture of a cyclic organohydrogensiloxane and a compound having at least two phenyl units and one alkenyl unit is used as the binder.

[0014] EP 2 603 562 B1 also describes a self-adhesive, addition-crosslinking silicone composition that contains as a binder a mixture of a cyclic organohydrogensiloxane and an organic compound having at least two aliphatically unsaturated groups per molecule. According to the teaching of EP 2 603 562 B1, this combination provides very good adhesion, especially to bisphenol A-containing thermoplastics.

[0015] Many self-adhesive crosslinkable silicone compositions are known from the prior art. However, known solutions show that good adhesion to a specific substrate is highly dependent on the binder used. A further problem is that most of the described additives that promote adhesion, which are added to silicone compositions, contain phenylsilyl or alkoxysilyl groups, and therefore these or their hydrolysis products are toxic and harmful to health. This limits their use to industrial materials. These materials are not suitable for pharmaceutical, cosmetic or food-related applications. [Prior art documents] [Patent documents]

[0016] [Patent Document 1] European Patent No. 0961811 [Patent Document 2] DE 102007044789 [Patent Document 3] European Patent No. 2603562 Summary of the Invention [Problem to be solved by the invention]

[0017] It is therefore an object of the present invention to provide a silicone composition, which is used in a process for coating the surface of a substrate or for producing a composite moulded article, which shows particularly good adhesion to the base but at the same time does not adhere troublesomely to processing equipment, such as injection moulding equipment, so that the moulded article can be easily demoulded and is not damaged in any way during processing, and whereby high processing stability is achieved. [Means for solving the problem]

[0018] The present invention therefore provides an addition crosslinkable silicone rubber composition comprising: (A) at least one organopolysiloxane having at least two aliphatic double bonds in the molecule; (B) at least one organopolysiloxane having at least three Si-H groups in the molecule, the Si-H content being at least 0.45% by weight and not more than 1.3% by weight; (C) at least one hydrosilylation catalyst; (D) at least one binder of general formula (I) [H 2 C=CH-(A 1 ) z -(A 2 ) m -X] n B (I) Where: A 1 is a divalent C which is unsubstituted or substituted by a halogen atom 1 -C 18 is a hydrocarbon group, A 2 are non-adjacent oxygen or nitrogen atoms, or are of the formula -NR-, -CO- or -CO-NR 1- or -, and is unsubstituted or substituted by halogen atoms. 1 -C 24 a hydrocarbon group, provided that there are at least 5 carbon atoms per oxygen or nitrogen atom; X is a divalent group -O-, -CO- or -COO-, B is a polar group containing a carbon atom and at least two non-adjacent oxygen atoms, where the oxygen atoms are present as oxygen or as a hydroxyl group, C 1 -C 4 -Acyl group or C 1 -C 3 in a trialkylsilyl group, provided that there are not more than 3 carbon atoms per oxygen atom; m is 0 or 1, preferably 0; n is 2, z is 0 or 1; R and R 1 each is a monovalent C which is unsubstituted or substituted by a halogen atom 1 -C 10 is a hydrocarbon group, However, the group [H 2 C=CH-(A 1 ) z -(A 2 ) m -X] are the same or different; And, (E) NO cyclic organohydrogenpolysiloxanes of general formula (III): (SiHR 7 O) g (SiR 8 R 9 O) k (III), Where: R 7 is hydrogen or R 8 is identical to, and R 8 and R 9 are each independently of the other, (a) a monovalent aliphatic saturated hydrocarbon group having 1 to 20 carbon atoms, or (b) having 6 to 20 carbon atoms and at least one aromatic C 6 a halogen-substituted or unsubstituted monovalent hydrocarbon group containing a ring; Or, (c) a monovalent cycloaliphatic halogen-substituted or unsubstituted hydrocarbon radical having 3 to 20 carbon atoms; Or, (d) a halogen substituent, a saturated group, or a monovalent hydrocarbon group having 2 to 20 carbon atoms and which may or may not contain an O atom or a N atom; Or, (e) a linear, cyclic or branched group that contains a Si atom and may or may not have one or more Si-bonded hydrogen atoms; g is 1 or greater, and k is 0 or a positive integer, preferably 0, 1, 2, particularly preferably 0; However, the sum of g and k is 4 or greater. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] In order to avoid overloading the description of the present invention, only preferred embodiments of the individual features for each component are shown.

[0020] Those skilled in the art should expressly interpret such disclosure as implying that all combinations of different priorities (i.e., any combination both within one component and between different components) are expressly disclosed as examples and are expressly preferred.

[0021] Component (A) has long been known to those skilled in the art. Organopolysiloxanes having at least two aliphatic double bonds in the molecule are preferred. These preferably have SiC-bonded C 1 -C 6-C containing alkyl groups, in particular methyl and / or phenyl groups, and containing an aliphatic double bond 1 -C 6 -Alkenyl groups. Preferred alkenyl groups are vinyl and allyl groups. The molecule preferably contains 10 or fewer alkenyl groups.

[0022] The organopolysiloxane (A) is preferably linear. The viscosity of (A) is guided by the desired viscosity of the formulated silicone composition or by the mechanical profile of the moldings that can be produced therefrom, and is preferably 200 to 200,000 mPa·s at 20°C.

[0023] When no optional components are present, the amount of (A) in the silicone composition of the present invention is typically 50-80% by weight, preferably 60-70% by weight. When optional components are present, the amount of (A) is correspondingly reduced.

[0024] Component (B) has also been known to those skilled in the art for a long time. It is an organopolysiloxane having at least three Si-H groups in the molecule, preferably having not only Si-H groups but also SiC bonds. 1 -C 6 -alkyl groups, in particular methyl and / or phenyl groups. The organopolysiloxane (B) is preferably linear.

[0025] It is important that the Si-H content of (B) is at least 0.45% by weight and not more than 1.3% by weight, preferably at least 0.7% by weight and preferably not more than 1.2% by weight.

[0026] The viscosity of the organopolysiloxane (B) at 20° C. is preferably from 5 to 50,000 mPa·s, particularly from 10 to 5,000 mPa·s, and particularly preferably from 15 to 100 mPa·s.

[0027] A preferred embodiment of the organopolysiloxane (B) is, for example, H(CH 3 )SiO 2 / 2 and (CH 3 ) 3 SiO 1 / 2 End group (CH 3 ) 2 SiO 2 / 2 A copolymer comprising units, H(CH 3 )SiO 2 / 2 and H(CH 3 ) 2 SiO 1 / 2 End group (CH 3 ) 2 SiO 2 / 2 A copolymer comprising units, (Ph) 2 SiO 2 / 2 and (CH 3 ) 3 SiO 1 / 2 H(CH 3 )SiO 2 / 2 A copolymer comprising units, (Ph) 2 SiO 2 / 2 , (CH 3 ) 2 SiO 2 / 2 and (CH 3 ) 3 SiO 1 / 2 H(CH 3 )Si 2 / 2 A copolymer comprising units, (Ph)SiO 3 / 2 , (CH 3 ) 2 SiO 2 / 2 and (CH 3 ) 3 SiO 1 / 2 H(CH 3 )Si 2 / 2 A copolymer comprising units, (Ph)(CH 3 )SiO 2 / 2 , (CH 3 ) 2 SiO 2 / 2 and (CH 3 ) 3 SiO 1 / 2 H(CH 3)Si 2 / 2 A copolymer comprising units, (Ph)(CH 3 )SiO 2 / 2 , (CH 3 ) 2 SiO 2 / 2 and H(CH 3 ) 2 SiO 1 / 2 H(CH 3 )Si 2 / 2 A copolymer comprising units, (Ph)(CH 3 )SiO 2 / 2 and (CH 3 ) 3 SiO 1 / 2 H(CH 3 )Si 2 / 2 A copolymer comprising units, -Si(CH 3 ) 2 -C 6 H 4 -Si(CH 3 ) 2 O 2 / 2 -, (CH 3 ) 2 SiO 2 / 2 and H(CH 3 )HSiO 1 / 2 Copolymers comprising units, -Si(CH 3 ) 2 -C 6 H 4 -Si(CH 3 ) 2 O 2 / 2 - and (CH 3 )HSiO 2 / 2 It is a copolymer containing units.

[0028] Particularly preferred embodiments of the organopolysiloxane (B) are, for example, H(CH 3 )SiO 2 / 2 and (CH 3 ) 3 SiO 1 / 2 End group (CH 3 ) 2 SiO 2 / 2 Copolymers comprising units, (Ph)SiO 3 / 2 , (CH 3 ) 2 SiO 2 / 2 and (CH 3 ) 3 SiO 1 / 2 H(CH 3 )Si 2 / 2 It is a copolymer containing units.

[0029] The amount of (B) in the silicone composition of the present invention is typically 0.1 to 10% by weight, preferably at least 0.3% by weight and particularly preferably at least 0.5% by weight, and preferably no more than 5% by weight and particularly preferably no more than 3% by weight.

[0030] The ratio of SiH from component (B) to the total number of Si-vinyl bond groups in the addition crosslinkable silicone rubber composition is preferably within the range of 0.5 to 5, and particularly preferably 0.6 to 1.8.

[0031] Component (C) has likewise been known to the skilled artisan for a long time. These are noble metal catalysts, in particular metals selected from the group consisting of platinum, rhodium, palladium, ruthenium and iridium, and their compounds, in particular platinum and / or its compounds. All catalysts which have been used up to now for the addition of Si-H groups to aliphatically unsaturated compounds can be used here. Examples of such catalysts are metallic and finely divided platinum, platinum compounds or complexes, which may be present on supports such as silicon dioxide, aluminum oxide or activated carbon, for example platinum halides, for example PtCl 4 , H 2 PtCl 6 .6H 2 O, Na 2 PtCl 4 .4H 2 O, platinum-olefin complex, platinum-alcohol complex, platinum-alkoxide complex, platinum-ether complex, platinum-aldehyde complex, H 2 PtCl 6 .6H 2Platinum-ketone complexes, including the reaction product of O with cyclohexanone, platinum-vinylsiloxane complexes, such as platinum-divinyltetramethyldisiloxane complexes, with or without a detectable content of organically bound halogens, bis(gamma-picoline)platinum dichloride, trimethylenedipyridine platinum dichloride, dicyclopentadiene platinum dichloride, (dimethylsulfoxide)diethyleneplatinum(II) dichloride, and also the reaction products of platinum tetrachloride with olefins and primary or secondary amines or primary and secondary amines, such as the reaction products of platinum tetrachloride dissolved in 1-octene with sec-butylamine, or ammonium-platinum complexes. UV-activated hydrosilylation catalysts may also be used.

[0032] The hydrosilylation catalyst (C) can be used in any form, for example in the form of microcapsules containing hydrosilylation catalyst or polyorganosiloxane particles. The content of the hydrosilylation catalyst (C) is preferably selected so that the addition-crosslinkable composition of the present invention has a Pt content of 0.1 to 200 ppm by weight, in particular 0.5 to 40 ppm by weight.

[0033] Component (D) is a binder of general formula (I): [H 2 C=CH-(A 1 ) z -(A 2 ) m -X] n B (I) Where: A 1 is a divalent C which is unsubstituted or substituted by a halogen atom 1 -C 18 is a hydrocarbon group, A 2 represents non-adjacent oxygen or nitrogen atoms or a group of the formula -NR-, -CO- or -CO-NR 1 - or -, and is unsubstituted or substituted by halogen atoms. 1 -C24 a hydrocarbon group, provided that there are at least 5 carbon atoms per oxygen or nitrogen atom; X is a divalent group -O-, -CO- or -COO-, B is a polar group containing a carbon atom and at least two non-adjacent oxygen atoms, where the oxygen atoms are present as ether oxygens or as hydroxyl groups, C 1 -C 4 -Acyl group or C 1 -C 3 in a trialkylsilyl group, provided that there are not more than 3 carbon atoms per oxygen atom; m is 0 or 1; n is 2, z is 0 or 1; R and R 1 each is a monovalent C which is unsubstituted or substituted by a halogen atom 1 -C 10 is a hydrocarbon group, However, the group [H 2 C=CH-(A 1 ) z -(A 2 ) m -X] are the same or different.

[0034] Binders (D) are in part commercially available or are prepared by common conventional methods of synthetic organic chemistry.

[0035] Divalent C 1 -C 18 Hydrocarbon group A 1 A may be saturated, aliphatically unsaturated, aromatic, linear or branched. 1 Preferably, it has 3 to 13 carbon atoms.

[0036] In the preferred binder (D), m in formula (I) is 0, and therefore A 2 does not exist.

[0037] The two X groups present in the molecule (I) may be the following groups: two -O-; one -O- and one -COO-; one -COO- and one -CO-; two -CO-; two -COO-. In chemical terms, the two X groups may form, together with the B group, for example, a diether, an ether and an ester or a diester. Diesters are preferred.

[0038] (D) preferably has at least 4 oxygen atoms, in particular at least 6 oxygen atoms.

[0039] Preferred binders (D) are the diesters of the following glycols, such as oligo- or polyalkylene glycols, with the following organic acids: Glycol: ● Oligoethylene or polyethylene glycol ● Oligoethylene or polypropylene glycol ● Ethylene glycol / propylene glycol copolymer ● Ethylene glycol / isopropylene glycol copolymer ● Oligoisopropylene or polyisopropylene glycol

[0040] Particularly preferred are diesters of oligoethylene or polyethylene glycol, where the oligoethylene or polyethylene glycol may consist essentially of a pure substance, i.e. have a certain number of repeating units, or the oligoethylene or polyethylene glycol may have a molecular weight distribution, i.e. be a mixture of substances with different molecular weight distributions, which can be detected by gel permeation chromatography.

[0041] Organic acids having at least one terminal double bond are, for example: Acrylic acid ● 3-Butenoic acid ● 4-Pentenoic acid ● 5-Hexanoic acid ● 6-heptenoic acid ● 7-octenoic acid ● 8-Nonenoic acid ● 9-Decenoic acid ● 10-Undecenoic acid ● 11-dodecenoic acid ● 12-Tridecenoic acid ● 13-Tetradecenoic acid ● 14-Pentadecenoic acid ● 15-Hexadecenoic acid etc.

[0042] Multiply unsaturated and / or branched carboxylic acids are also possible, however, those in which at least one double bond is in a terminal position are preferred.

[0043] Further preferred binders are the monoesters of the following glycols, for example oligoalkylene or polyalkylene glycols, etherified at one end with an aliphatic unsaturated hydrocarbon group having 2 to 16 carbon atoms, such as vinyl, allyl or a longer chain group: ● Oligoethylene or polyethylene glycol monoallyl ether ● Oligoethylene or polyethylene glycol monovinyl ether ● Oligopropylene or polypropylene glycol monoallyl ether ● Oligopropylene or polypropylene glycol monovinyl ether ● Ethylene glycol / propylene glycol monoallyl ether copolymer ● Ethylene glycol / propylene glycol monovinyl ether copolymer ● Ethylene glycol / isopropylene glycol monoallyl ether copolymer ● Ethylene glycol / isopropylene glycol monovinyl ether copolymer ● Oligoisopropylene or polyisopropylene glycol monoallyl ether ● Oligoisopropylene or polyisopropylene glycol monovinyl ether Here, the monoester is formed with the abovementioned acids.

[0044] Particularly preferred binders (D) are: ● Terminal unsaturated C of oligoethylene glycol 6 -C 16 Diesters with carboxylic acids, in particular with 10-undecenoic acid. Oligo-ethylene glycols are diesters of 2 to 40 ethylene glycol units -[CH 2 -CH 2 -O]-, preferably 3 to 20 ethylene glycol units -[CH 2 -CH 2 -O]-, especially 4 to 10 ethylene glycol units -[CH 2 -CH 2 -O]-.

[0045] The silicone compositions contain at least 0.05% by weight of (D), preferably at least 0.1% by weight of (D). Furthermore, they contain no more than 10% by weight of (D), preferably no more than 4% by weight of (D).

[0046] Component (E) is not present because the desired good adhesion to the substrate is surprisingly achieved without component (E) while at the same time having a lower, i.e. reversible, adhesion to processing equipment, such as injection molding tools.

[0047] The addition-crosslinkable silicone composition of the present invention may further comprise at least one filter (F) as a further component. Suitable filters are known to those skilled in the art. 2 Non-reinforced filters (F) having a BET surface area of ​​up to 50 m / g are, for example, quartz, diatomaceous earth, talc, calcium silicate, zirconium silicate, zeolites, metal oxide powders such as aluminum oxide, titanium oxide, iron oxide or zinc oxide and mixed oxides thereof, barium sulfate, calcium carbonate, gypsum, silicon nitride, silicon carbide, boron nitride, glass and polymer powders. Reinforced filters, i.e. filters having a BET surface area of ​​at least 50 m / g, are, for example, quartz, diatomaceous earth, talc, calcium silicate, zirconium silicate, zeolites, metal oxide powders such as aluminum oxide, titanium oxide, iron oxide or zinc oxide and mixed oxides thereof, barium sulfate, calcium carbonate, gypsum, silicon nitride, silicon carbide, boron nitride, glass and polymer powders. 2 / g, especially 100-400m 2Filters with a BET surface area of ​​1000 nm / g are, for example, pyrogenic silica, precipitated silica, aluminum hydroxide, carbon blacks such as furnace black and acetylene black, and silicon-aluminum mixed oxides with a large BET surface area. The above-mentioned filter (F) may be hydrophilized, for example by treating with organosilanes, organosilazanes or organosiloxanes, or by etherifying hydroxyl groups to form alkoxy groups. One type of filter (F) can be used, but it is also possible to use a mixture of at least two types of filters (F). The silicone composition of the present invention preferably comprises at least 3% by weight, particularly preferably at least 5% by weight, in particular at least 10% by weight, and not more than 50% by weight of the filter (F).

[0048] The silicone composition of the present invention may optionally contain additives as further constituent (G) in a proportion of 0 to 70% by weight, preferably 0.0001 to 40% by weight. These additives are known to the person skilled in the art and may be, for example, resin-like polyorganosiloxanes different from the polyorganosiloxanes (A) and (B) and of course (H), dispersants, solvents, binders, pigments, dyes, plasticizers, organic polymers, heat stabilizers and inhibitors. Furthermore, thixotropic constituents, such as finely divided silica or other commercially available thixotropic additives, may be present as constituents.

[0049] Furthermore, further additives may be present which contribute to setting in a targeted manner the processing time, the initiation temperature and the crosslinking rate of the crosslinkable composition. These inhibitors and stabilizers are well known in the field of crosslinkable compositions.

[0050] The silicone composition of the present invention may optionally contain as further component (H) an organopolysiloxane having at least two SiH groups in the molecule and different from component (B). These are preferably SiC-bonded C 1 -C 6-alkyl groups, in particular methyl and / or phenyl groups, in addition to the Si-H groups, are predominantly linear organopolysiloxanes. The organopolysiloxanes (H) preferably have terminal SiH groups. In the case of component (A), the viscosity of the organopolysiloxane (H) is guided by the desired viscosity of the formulated silicone composition and the mechanical profile of the vulcanizates produced therefrom and is between 10 and 200000 mPa·s, preferably between 15 and 10000 mPa·s at 20°C.

[0051] Examples of organopolysiloxanes (H) are dimethylsiloxy-terminated polydimethylsiloxanes and dimethylsiloxy-terminated copolymers of dimethylsiloxy and methylphenylsiloxy units.

[0052] The amount of component (H) in the silicone composition of the present invention is typically 0 to 50% by weight, and preferably 0 to 25% by weight.

[0053] Overall, the amounts of all components are always selected to combine to total 100% by weight in the silicone composition of the present invention.

[0054] The present invention further provides a method for producing the addition crosslinkable silicone composition of the present invention. The production or compounding of the silicone composition of the present invention is preferably carried out by mixing components (A)-(D) with or without (F) and / or (G) and / or (H). The composition of the present invention can be produced as a one-component composition, a two-component composition or a multi-component composition. Crosslinking is carried out by heating or irradiation with a suitable light source, depending on the catalyst.

[0055] The present invention further provides a method for coating a substrate surface and for producing a composite molded article, comprising the steps of: a) a substrate surface is coated with a silicone rubber composition, or / and a substrate and / or a combination of substrates is assembled and a silicone rubber composition is introduced into an intermediate region; b) The silicone rubber composition is then cured, c) A demolding operation is then carried out, wherein the silicone rubber composition is an addition crosslinkable silicone rubber composition comprising: (A) at least one organopolysiloxane having at least two aliphatic double bonds in the molecule; (B) at least one organopolysiloxane having at least three Si-H groups in the molecule, the Si-H content being at least 0.45% by weight and not more than 1.3% by weight; (C) at least one hydrosilylation catalyst; (D) at least one binder of general formula (I) [H 2 C=CH-(A 1 ) z -(A 2 ) m -X] n B (I) Where: A 1 is a divalent C which is unsubstituted or substituted by a halogen atom 1 -C 18 is a hydrocarbon group, A 2 are non-adjacent oxygen or nitrogen atoms, or are of the formula -NR-, -CO- or -CO-NR 1 - or -, and is unsubstituted or substituted by halogen atoms. 1 -C 24 a hydrocarbon group, provided that there are at least 5 carbon atoms per oxygen or nitrogen atom; X is a divalent group -O-, -CO- or -COO-, B is a polar group containing a carbon atom and at least two non-adjacent oxygen atoms, where the oxygen atoms are present as oxygen or as a hydroxyl group, C 1 -C 4 -Acyl group or C 1 -C 3in a trialkylsilyl group, provided that there are not more than 3 carbon atoms per oxygen atom; m is 0 or 1 (preferably 0); n is 2, z is 0 or 1; R and R 1 each is a monovalent C which is unsubstituted or substituted by a halogen atom 1 -C 10 is a hydrocarbon group, However, the group [H 2 C=CH-(A 1 ) z -(A 2 ) m -X] are the same or different; And, (E) NO cyclic organohydrogenpolysiloxanes of general formula (III): (SiHR 7 O) g (SiR 8 R 9 O) k (III), Where: R 7 is hydrogen or R 8 is the same as R 8 and R 9 are each independently of the other, (a) a monovalent aliphatic saturated hydrocarbon group having 1 to 20 carbon atoms, Or, (b) having 6 to 20 carbon atoms and at least one aromatic C 6 a halogen-substituted or unsubstituted monovalent hydrocarbon group containing a ring; Or, (c) a monovalent cycloaliphatic halogen-substituted or unsubstituted hydrocarbon radical having 3 to 20 carbon atoms; Or, (d) a halogen substituent, a saturated group, or a monovalent hydrocarbon group having 2 to 20 carbon atoms and which may or may not contain an O atom or a N atom; Or, (e) a linear, cyclic or branched group containing a silicon atom and having or not having one or more silicon-bonded hydrogen atoms; g is 1 or greater, and k is 0 or a positive integer, preferably 0, 1, 2, particularly preferably 0; However, the sum of g and k is 4 or greater.

[0056] The substrate is a thermoplastic, preferably polyamide, polycarbonate and polybutylene terephthalate, particularly preferably polycarbonate.

[0057] The present invention further provides coated substrates and composite mouldings obtainable by the process of the present invention.

[0058] Surprisingly, it has been found that only the combination of (B) with selected Si-H content in combination with specific binder (D) produces a synergistic effect, firstly, with very good adhesion to substrates made of rigid thermoplastics such as polyamide, polycarbonate and polybutylene terephthalate, and secondly, with very poor adhesion to injection molding tools made of steel, for example.It is unexpected that no further component (E) is required to achieve this, and it is contrary to the teaching of EP2190927B1.In the process for coating substrate surfaces and for producing composite moldings, the composition of the present invention allows a very reliable demolding operation, resulting in less breakdowns and therefore achieving an overall high production stability.This leads to an improvement in the economics of production plants. EXAMPLES

[0059] The following examples describe how the invention can in principle be put into practice, but do not limit the invention to the content disclosed therein.

[0060] All percentages are percentages by weight. Unless otherwise indicated, all operations are carried out at room temperature (about 20° C.) and atmospheric pressure (about 1.013 bar). Equipment is commercial laboratory equipment and can be purchased from a number of equipment manufacturers.

[0061] Base Material The adhesion of silicone compositions according to the invention and not according to the invention to the following substrates was tested: ● Polycarbonate: Makrolon(R)2405 (Bayer MaterialScience AG) ● Polybutylene terephthalate (PBT): Pocan(R)B 1305 (Lanxess) ● V2A steel (industrial grade)

[0062] Prior to the preparation of the test specimens for the separation force measurements, the base material for the press-vulcanization process and the thermoplastic granules for the injection molding process were dried in a suitable manner according to the manufacturer's instructions. For the press-vulcanization process, the test specimens were additionally degreased beforehand.

[0063] Adhesion characterization The preparation of test specimens for the separation force measurements was first carried out under laboratory conditions by a press vulcanization process. Further test specimens were prepared under practical manufacturing conditions by a two-component injection molding process.

[0064] For the preparation by press vulcanization, a suitable stainless steel mold, preferably manufactured by injection molding and having a size of 60×25×2 mm, is used, into which the substrate is placed, and then each mold is filled with the addition crosslinking silicone composition to be tested. For the base material polycarbonate, vulcanization is carried out at a temperature of 120° C. and a pressing force of 30 metric tons for 3 minutes, causing complete crosslinking of the liquid silicone composition. If the base material is V2A, vulcanization is carried out at 180° C. for 5 minutes. After that, all test specimens are cooled to room temperature. The test specimens made in this way, consisting of a substrate and a 2.5 mm thick liquid silicone elastomer layer, are removed from the mold and then first stored at room temperature for at least 16 hours. After that, the test specimens are clamped in a tensile test device, and the maximum separation force for peeling off the silicone elastomer pieces that are bonded is determined.

[0065] The preparation of test specimens by the two-component injection molding process was carried out using an injection molding machine according to the prior art using a rotating plate device, where the thermoplastic base was first produced and transferred to the injection molding device by a second rotating plate. In the next processing step, the silicone composition was sprayed onto the finished thermoplastic base and vulcanized to the substrate. The injection pressure for the self-adhesive, addition-crosslinking silicone composition is usually in the range of 200-2000 bar, but in certain cases these values ​​may be lower or higher. The injection temperature for the self-adhesive, addition-crosslinking silicone composition is usually in the range of 15-50° C., likewise in individual cases the temperature may be lower or higher than these temperatures.

[0066] The test specimens produced by a two-component injection moulding process and used to evaluate the strength of adhesion of the silicone elastomers according to the invention to substrates are given in DIN ISO 813.

[0067] Prior to adhesion testing, the test specimens made by the two-component injection molding process were likewise stored at room temperature for at least 16 hours. Adhesion testing and crack formation evaluation were carried out in the same manner as for the test specimens from the press cure.

[0068] Quantification of adhesion of composites consisting of silicone elastomer and thermoplastic base was carried out by a method based on the adhesion test according to DIN ISO 813, where the 90° peel method was carried out using the substrate and silicone elastomer pieces at an angle of 90° to each other and a peel speed of preferably 50 mm / min. The determined separation force (SF) was reported in N / mm as the ratio of the maximum force N to the width of the test specimen. According to the examples, 3 to 5 thin layers were measured and the separation force was determined as an average.

[0069] Base composition 1 232 g of a vinyldimethylsiloxy-terminated polydimethylsiloxane having a viscosity of 20,000 mPa·s (25°C) was placed in a commercial laboratory kneader and heated to 150°C to produce 159 g of a 300 m 2 The silica particles were mixed with hydrophobic pyrogenic silica having a specific surface area of ​​0.1 g / g (measured by BET method) and a carbon content of 3.9-4.2 wt%.

[0070] This resulted in a very viscous composition, which was diluted with 130 g of the above-mentioned polydimethylsiloxane. The resulting composition was kneaded for 1 hour at 150° C. under reduced pressure (10 mbar) to remove water and excess loading agent residues, especially volatile components.

[0071] Base composition 2 202 g of vinyldimethylsiloxy-terminated polydimethylsiloxane having a viscosity of 20,000 mPa·s (25°C), 45 g of hexamethyldisilazane, and 15 g of water were placed in a commercial laboratory kneader and mixed to produce 150 g of 300 m 2 Hydrophilic pyrogenic silica with a specific surface area of ​​1000 g / g (measured by the BET method) was added, which gave a very viscous composition, which was kneaded for 2 hours at 150° C. under reduced pressure (10 mbar) to remove water and excess loading agent residues, especially volatile constituents, and diluted with 110 g of the above-mentioned vinyl-terminated polydimethylsiloxane.

[0072] Base composition 3 235 g of a vinyldimethylsiloxy-terminated polydimethylsiloxane having a viscosity of 20,000 mPa·s (at 25°C) and 24 g of an OH-terminated polydimethylsiloxane having a viscosity of 40 mPa.s were placed in a commercial laboratory kneader. During heating to 150°C, 143 g of a 200 m 2 Precipitated silica with a specific surface area of ​​1000 g / g (measured by the BET method) was added. This resulted in a very viscous composition, which was then diluted with 90 g of the above-mentioned vinyl-terminated polydimethylsiloxane. The resulting composition was kneaded at 150° C. under reduced pressure (10 mbar) for 1 hour to remove volatile constituents.

[0073] A-Component 1 345.8 g of Base Composition 1 was mixed with 3.5 g of a dimethylvinylsiloxy-terminated polydimethylsiloxane having methylvinylsiloxy groups, a vinyl content of 2.5 mmol / g, and a viscosity of 340 mPa·s, and 0.7 g of a catalyst solution containing a platinum-divinyltetramethyldisiloxane complex in a silicone polymer and having a Pt content of 1 wt %.

[0074] Crosslinker 1 A trimethylsiloxy-terminated copolymer of dimethylsiloxy and methylhydrogensiloxy units (0.4:1 molar ratio) having a viscosity of 35 mPa·s and a SiH content of 1.1 wt.%.

[0075] Crosslinker 2 A trimethylsiloxy terminated copolymer of dimethylsiloxy and methylhydrogensiloxy units (2:1 molar ratio) having a viscosity of 115 mPa·s and a SiH content of 0.5 wt.%.

[0076] Crosslinker 3 A trimethylsiloxy terminated copolymer of dimethylsiloxy, methylhydrogensiloxy and phenylsiloxy units (molar ratio of 0.33:1:0.18) having a viscosity of 80 mPa·s and a SiH content of 0.9 wt%.

[0077] Crosslinker 4 A trimethylsiloxy terminated copolymer of dimethylsiloxy, methylhydrogensiloxy and phenylsiloxy units (molar ratio of 0.36:1:0.12) having a viscosity of 18 mPa·s and a SiH content of 0.9 wt%.

[0078] Crosslinker 5 A trimethylsiloxy-terminated copolymer of dimethylsiloxy and methylhydrogensiloxy units (9:1 molar ratio) having a viscosity of 150 mPa·s and a SiH content of 0.14 wt.%.

[0079] Crosslinker 6 A trimethylsiloxy-terminated polymethylhydrogensiloxane with a viscosity of 25 mPa·s and a SiH content of 1.6 wt.%.

[0080] Binder 1 42.5 g of polyethylene glycol 200 (available from Merck) was added to 85.0 g of 10-undecenoic acid chloride (available from Merck) with stirring at 80° C. over a period of 30 minutes, and stirring was continued until gas evolution was no longer noticeable. After addition of 1.7 g of hexamethyldisilazane, the mixture was heated at 80° C. under reduced pressure (<4 mbar) for 1 hour. After cooling, the residue was filtered through Dicalite filter aid. 94 g of a clear yellow-orange liquid was obtained. 1 The 1 H-NMR spectrum corresponded to the bis-10-undecene ester of polyethylene glycol 200.

[0081] Binder 2 204.9 g of polyethylene glycol 300 (available from Merck) was placed in a flask at 80° C. and 208.0 g of undecenoic acid chloride (available from Merck) was added over 45 minutes. After the addition was complete, the mixture was stirred at 80° C. for 30 minutes. Then, 13.7 g of hexamethyldisilazane was added at 80° C. and the mixture was stirred for another 5 minutes. The reaction mixture was heated at 120° C. and 1 mbar for 1 hour. The residue was cooled to room temperature and filtered through Dicalite filter aid. 360.9 g of a clear yellow liquid was obtained.1 The 1 H-NMR spectrum corresponded to the bis-10-undecene ester of polyethylene glycol 300.

[0082] The A- and B-components from the examples are intensively mixed, for example in a Speedmixer (Hauschild) and this mixture is applied to the substrate in a mould.

[0083] Withdrawal force values ​​of more than 10 N / mm for polycarbonate for test specimens prepared as described above in a press mould are considered satisfactory.

[0084] Withdrawal force values ​​below 2 N / mm for V2A steel for test specimens prepared as described above in a press mould are deemed sufficiently low to correspond to a formulation that will not build up troublesome adhesion to the injection moulding equipment in an industrial injection moulding process.

[0085] Example 1 (according to the present invention) A-component 1 was used as the A-component.

[0086] B-Components: 95 g of Base Composition 2 was mixed with 0.1 g of 1-ethynyl-1-cyclohexanol, 3 g of Crosslinker 3 and 1.5 g of Binder 1.

[0087] Vulcanizate: Shore A 42 Adhesion to Makrolon 2405: 11.7 N / mm, with bond cracking Adhesion to V2A: 1.6N / mm, with adhesive cracks

[0088] Example 2 (according to the present invention) A-component 1 was used as the A-component.

[0089] B-Components: 95 g of Base Composition 2 was mixed with 0.1 g of 1-ethynyl-1-cyclohexanol, 3 g of Crosslinker 3 and 0.75 g of Binder 2.

[0090] Vulcanizate: Shore A 41 Adhesion to Makrolon 2405: 10.9 N / mm, with bond cracking Adhesion to V2A: 1.2N / mm, with adhesive cracks

[0091] Example 3 (according to the present invention) A-component 1 was used as the A-component.

[0092] B-Components: 95 g of Base Composition 2 was mixed with 0.1 g of 1-ethynyl-1-cyclohexanol, 2.7 g of Crosslinker 4 and 0.75 g of Binder 2.

[0093] Vulcanizate: Shore A 42 Adhesion to Makrolon 2405: 12.9 N / mm with bond cracking Adhesion to V2A: 0N / mm, with adhesive cracks

[0094] Example 4 (according to the present invention) A-component 1 was used as the A-component.

[0095] B-Components: 95 g of Base Composition 2 was mixed with 0.1 g of 1-ethynyl-1-cyclohexanol, 3.0 g of Crosslinker 3 and 1.0 g of Binder 2.

[0096] Vulcanizate: Shore A 51 Adhesion to Makrolon 2405: 14.8 N / mm, with bond cracking Adhesion to V2A: 0.2N / mm, with adhesive cracks

[0097] Example 5 (according to the present invention) A-component 1 was used as the A-component.

[0098] B-Components: 95 g of Base Composition 1 was mixed with 0.1 g of 1-ethynyl-1-cyclohexanol, 2.8 g of Crosslinker 3 and 1.3 g of Binder 1.

[0099] Vulcanizate: Shore A 40 Adhesion to Makrolon 2405: 10.7 N / mm, with bond cracking Adhesion to V2A: 1.3N / mm, with adhesive cracks

[0100] Example 6 (according to the present invention) A-component 1 was used as the A-component.

[0101] B-Components: 96.5 g of Base Composition 3 was mixed with 0.1 g of 1-ethynyl-1-cyclohexanol, 2.7 g of Crosslinker 4 and 0.8 g of Binder 1.

[0102] Vulcanizate: Shore A 40 Adhesion to Makrolon 2405: 11.9 N / mm, with bond cracking Adhesion to V2A: 1.6N / mm, with adhesive cracks

[0103] Example 7 (according to the invention) A-component 1 was used as the A-component.

[0104] B-Components: 96.5 g of Base Composition 3 was mixed with 0.1 g of 1-ethynyl-1-cyclohexanol, 2.5 g of Crosslinker 1 and 1.0 g of Binder 1.

[0105] Vulcanizate: Shore A 40 Adhesion to Makrolon 2405: 11.3 N / mm, with bond cracking Adhesion to V2A: 1.8N / mm, with adhesive cracks

[0106] Example 8 (according to the present invention) A-component 1 was used as the A-component.

[0107] B-Components: 61 g of Base Composition 2 was mixed with 0.02 g of 1-ethynyl-1-cyclohexanol, 25 g of a dimethylsiloxy-terminated polydimethylsiloxane having a viscosity of 950 mPas, 2.4 g of Crosslinker 4 and 0.5 g of Binder 1.

[0108] The A- and B-components are mixed in a Speedmixer in a 1:1 ratio with each other, applied to the substrate and vulcanized in a drying oven at 80° C. for 1 hour at atmospheric pressure. The vulcanizate has a Shore A hardness of 28. The composite shows no bond cracking to the silicone in the detachment test.

[0109] Example 9 (according to the invention) A-component 1 was used as the A-component.

[0110] B-Components: 95 g of Base Composition 2 was mixed with 0.1 g of 1-ethynyl-1-cyclohexanol, 2.7 g of Crosslinker 4 and 1.0 g of Binder 1.

[0111] The sample was processed by a two-component injection molding process.

[0112] Vulcanizate: Shore A 41 Adhesion to Makrolon 2405: 18.5 N / mm, with bond cracking Adhesion to Pocan 1305 (PBT): 16.2 N / mm, with bond cracks There is no adhesion to the template.

[0113] Example 10 (according to the invention) A-component 1 was used as the A-component.

[0114] B-Components: 95 g of Base Composition 2 was mixed with 0.1 g of 1-ethynyl-1-cyclohexanol, 2.5 g of Crosslinker 1 and 1.0 g of Binder 1.

[0115] The sample was processed by a two-component injection molding process.

[0116] Vulcanizate: Shore A 46 Adhesion to Makrolon 2405: 17.0 N / mm, with bond cracking Adhesion to Pocan 1305 (PBT): 13.8 N / mm, with bond cracks There is no adhesion to the template.

[0117] Example N.1 (not according to the invention) A-component 1 was used as the A-component.

[0118] B-Components: 95 g of Base Composition 2 was mixed with 0.1 g of 1-ethynyl-1-cyclohexanol, 2.3 g of Crosslinker 2, 1.50 g of the HD5 / HD6 ring mixture, and 2.0 g of diallyl adipate (obtained from ABCR).

[0119] Vulcanizate: Shore A 21 Adhesion to Makrolon 2405: 2.5N / mm, with adhesive cracking Adhesion to V2A: 2.4N / mm, with adhesive cracks

[0120] Example N.2 (not according to the invention) A-component 1 was used as the A-component.

[0121] B-Components: 95 g of Base Composition 2 was mixed with 0.1 g of 1-ethynyl-1-cyclohexanol, 3.0 g of Crosslinker 3, and 1.0 g of undecenoic acid esterified with monomethoxytriethylene glycol (ordered from Elevance under the designation u10MEE-03).

[0122] Vulcanizate: Shore A 40 Adhesion to Makrolon 2405: 0 N / mm, with adhesive cracks Adhesion to V2A: 1.9N / mm, with adhesive cracks

[0123] Example N.3 (not according to the invention) A-component 1 was used as the A-component.

[0124] B-Components: 95 g of Base Composition 2 was mixed with 0.1 g of 1-ethynyl-1-cyclohexanol, 7.1 g of Crosslinker 5 and 0.75 g of Binder 2.

[0125] Vulcanizate: Shore A 38 Adhesion to Makrolon 2405: 3.2 N / mm, with adhesive cracking Adhesion to V2A: 0.8N / mm, with adhesive cracks

[0126] Example N.4 (not according to the invention) A-component 1 was used as the A-component.

[0127] B-Components: 95 g of Base Composition 2 was mixed with 0.1 g of 1-ethynyl-1-cyclohexanol, 0.7 g of Crosslinker 6 and 0.75 g of Binder 2.

[0128] Vulcanizate: Shore A 47 Adhesion to Makrolon 2405: 6.9 N / mm, with mixed cracks Adhesion to V2A: 4.2N / mm, with mixed cracks

Claims

1. (A) at least one organopolysiloxane having at least two aliphatic double bonds in the molecule; (B) at least one organopolysiloxane having at least three Si—H groups in the molecule, the Si—H content being at least 0.45% by weight and not more than 1.3% by weight; (C) at least one hydrosilylation catalyst; and (D) An oligoethylene glycol having 2 to 40 ethylene glycol units -[CH 2 -CH 2 -O]- and a terminally unsaturated C carboxyl group having a structure other than the carboxyl group of H 2 C═CH-A 1 - (A 1 is a divalent C 3 -C 13 aliphatic saturated hydrocarbon group). 6 -C 16 at least one binder selected from diesters with carboxylic acids, An addition crosslinking silicone rubber composition comprising: (E) Cyclic organohydrogenpolysiloxanes of general formula (III): ()) 7 .) g ()) 8 ( 9 .) k (?).、 Where: R 7 is hydrogen or R 8 is identical to, and R 8 and R 9 are each independently of the other, (a) a monovalent aliphatic saturated hydrocarbon group having 1 to 20 carbon atoms; Or, (b) having 6 to 20 carbon atoms and at least one aromatic C 6 a halogen-substituted or unsubstituted monovalent hydrocarbon group containing a ring; Or, (c) a halogen-substituted or unsubstituted monovalent cycloaliphatic hydrocarbon group having 3 to 20 carbon atoms; Or, (d) a halogen-substituted, saturated monovalent hydrocarbon group having 2 to 20 carbon atoms and which may or may not contain O or N atoms; Or, (e) a linear, cyclic or branched group that contains a Si atom and may or may not have one or more Si-bonded hydrogen atoms; g is 1 or more, and k is 0 or a positive integer; However, the sum of g and k is 4 or greater. The addition-crosslinking silicone rubber composition of claim 1, wherein the silicone rubber composition does not contain any of the following:

2. 2. The addition-crosslinkable silicone rubber composition according to claim 1, wherein the viscosity of the organopolysiloxane (B) at 20° C. is 5 to 50,000 mPa·s.

3. 3. The addition-crosslinkable silicone rubber composition according to claim 1, wherein the carboxylic acid is 10-undecenoic acid.

4. Oligo-ethylene glycols are those that contain 3 to 20 ethylene glycol units -[CH 2 -CH 2 The addition-crosslinkable silicone rubber composition according to claim 3, characterized in that it has a group consisting of a cyclic alkyl group and a cyclic alkyl group.

5. 1. A method for coating a substrate surface or for producing a composite molded article, comprising the steps of: Where: a) the surface of a substrate is coated with a silicone rubber composition; and / or a substrate and / or a combination of substrates are assembled and the silicone rubber composition is introduced into the intermediate region; b) The silicone rubber composition is then cured, c) A demolding operation is then carried out, The silicone rubber composition is an addition crosslinkable silicone rubber composition containing the following (A) to (D): (A) at least one organopolysiloxane having at least two aliphatic double bonds in the molecule; (B) at least one organopolysiloxane having at least three Si—H groups in the molecule, the Si—H content being at least 0.45% by weight and not more than 1.3% by weight; (C) at least one hydrosilylation catalyst; (D) An oligoethylene glycol having 2 to 40 ethylene glycol units -[CH 2 -CH 2 -O]- and a terminally unsaturated C carboxyl group having a structure other than the carboxyl group of H 2 C═CH-A 1 - (A 1 is a divalent C 3 -C 13 aliphatic saturated hydrocarbon group). 6 -C 16 at least one binder selected from diesters with carboxylic acids, However, the addition-crosslinking silicone rubber composition does not contain the following (E): (E) Cyclic organohydrogenpolysiloxanes of general formula (III): ()) 7 .) g ()) 8 ( 9 .) k (?).、 Where: R 7 is hydrogen or R 8 is identical to, and R 8 and R 9 are each independently of the other, (a) a monovalent aliphatic saturated hydrocarbon group having 1 to 20 carbon atoms; Or, (b) having 6 to 20 carbon atoms and at least one aromatic C 6 a halogen-substituted or unsubstituted monovalent hydrocarbon group containing a ring; Or, (c) a halogen-substituted or unsubstituted monovalent cycloaliphatic hydrocarbon group having 3 to 20 carbon atoms; Or, (d) a halogen-substituted, saturated monovalent hydrocarbon group having 2 to 20 carbon atoms and which may or may not contain O or N atoms; Or, (e) a linear, cyclic or branched group that contains a Si atom and may or may not have one or more Si-bonded hydrogen atoms; g is 1 or more, and k is 0 or a positive integer; However, the sum of g and k is 4 or greater. A method for coating a substrate surface or for producing a composite moulded article.

6. 6. A method for coating the surfaces of substrates or for producing composite mouldings according to claim 5, characterized in that a thermoplastic is used as the substrate.

7. A coated substrate or composite moulding obtainable by the method according to claim 5 or 6.

Citation Information

Patent Citations

  • nsetzung

    DE102007044789A1

  • Polysiloxane compound which is stable during storage and produces vulcanisates which can be permanently wetted with water

    EP0961811A1

  • Self-adhesive silicone elastomers

    EP2603562A1

  • Curable organopolysiloxane composition

    JP1989174563A

  • Silicone rubber composition

    JP1996120177A